A cross-lagged analysis of the relationship between marital quality and depression among the older adults: gender effects of socioeconomic status - Fang, Bi-Ji; Leong, Kai-Seng; Tan, Hong-Xiu (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to explore the mechanism and gender effect of socioeconomic status on the relationship between marital quality and depression among the older adults, with the intention of providing a practical foundation for enhancing the quality of life of the older adults.MethodsThe data sourced from the third (conducted in 2015, denoted as the first survey) and fourth (carried out in 2018, regarded as the second survey) installments of the China Health and Retirement Longitudinal Survey (CHARLS) were meticulously analyzed through the utilization of cross-lagged analytical techniques and moderating effect examination methodologies.ResultsAmong the older adults, there exists a reciprocal causal relationship between marital quality and the level of depression. Specifically, the marital quality as measured in the first survey was found to significantly prognosticate the depression level in the second survey (β = 0.05, p < 0.05). Conversely, the depression level in the first survey was also demonstrated to significantly forecast the marital quality in the second survey (β = 0.15, p < 0.01). Regarding the moderating role of socioeconomic status, it was observed that among the older adult women, socioeconomic status exerted a moderating influence on the impact of depression on marital quality (β = 0.05, p < 0.05), whereas among the older adult men, their socioeconomic status failed to display a significant moderating effect (β = 0.02, p > 0.05). In a contrasting manner, for the older adult men, the socioeconomic status played a moderating role in the effect of marital quality on depression (β = −0.05, p < 0.01), while for the older adult women, it did not exhibit a moderating effect (β = −0.01, p > 0.05).ConclusionThere exists a reciprocal causal nexus between the marital quality and depression among the older adults. To enhance the life quality of the older adults, it behooves communities and families to proactively focus more on the older adults with subpar marital quality or afflicted by depression, and to disrupt the cyclic interplay between these two variables.